AB0525 NATURAL HISTORY OF CRYOGLOBULINEMIA FROM 2000 TO 2018 FROM THE LABORATORY POINT OF VIEW: AN ANALYSIS OF CRYOGLOBULIN CHARACTERISTICS IN A SINGLE CENTER. (2nd June 2020) - Sandri, G.; Spinella, A.; Natali, P.; Debbia, D.; Campioli, D.; Bari, A.; Amati, G.; Galassi, G.; Mazzoli, M.; Alfano, G.; Fontana, F.; Trenti, T.; et al.
Abstract : Background: Big data refers to large amounts of information. With today's ever-improving technologies created by the automation and digitization, it becomes easier to convert data into relevant information, which can be used to provide better patient management, especially when it occurs a rare condition such as cryoglobulinemia (CRG). CRG is due to an immunoglobulins (Ig) that precipitate at low temperatures. There are 3 types of CRG: type I: monoclonal Ig; type II: monoclonal Ig + polyclonal Ig; type III: 2 polyclonal Ig. Objectives: The aim of this study was to analyse the available data coming to the Department of Laboratory Medicine of Modena to describe the population of patients suffering of CRG. Methods: Data from the Modena Labs network were extracted by means of the software "Pagoda", for statistical purposes, directly connected to the Laboratories Information System (LIS). Considered time period 2000-2018 Results: The analysed samples were 28, 847, 4901 (17%) of which positive to the cryoglobulins (CR) detection. The typing positive CR were 4190 (85%): type 1 7.8 %, type II 48.54% and type III 43.8% The positive samples belonged to 2528 patients. Patients were 1563 (62%) women, average age 66±16, and 965 (38%) men, average age 62±16. (female/male ratio = 1.62) No statistically significant difference regarding sex and age between the 3 types. The cryoglobulinemia phenomenon is quite complex and the typing of monoclonal, polyclonal components of the Ig classes and chains has made it possible to identify 41 possible combinationsOut of 115 patients with Type 1 cryoglobulin, 73% had a monoclonal IgM and 36% monoclonal IgG; 11.2% both monoclonal IgG and IgM. The к light chain was the most frequent: 55, 6% IgM-k and 23, 4% IgG-k vs 29% IgM-λ and 18.2% IgG-λ. Two patients had an IgA-k cryoglobulin. Patients with Type 2 cryo were 781: monoclonal IgM-k 587 (75.1 %), 126 IgM-λ (16.1 %), 52 IgG-k (6.6 %), IgG-λ (5%), 1 IgA-λ; 2.8% had both IgG and IgM. Out of 1204 patients with Type 3 cryo, 74.8% had both polyclonal IgG and IgM, 13, 8% had isolated IgM or IgG (9%); 4.8 % IgG-IgA-IgM together, both IgG and IgA in only 0, 5% of patients. Almost the 50% (1255) of the patients had a diagnosis supporting the request of CR: HCV, 604 (48%); chronic hepatitis, 177 (14%); rheumatologic disorder, 107 (9%); autoimmune diseases, 83 (7%), nephropathy, 80 (7%); others, 204 (15%). Genotyped HCV+ patients were 290 (48%), with the following results: 1b, 136 (47%); 2a/2c, 65 (22%); 3a, 26 (9%); others 63 (22%). Conclusion: The data show that CRG is a pathology which affects the elderly and especially women, as in autoimmune and rheumatological diseases. The predominant CRG type is the III and the most frequently related pathology to the request for CR is HCV+ and chronic hepatitis. The most common HCV genotype are 1b and 2a/2c The cryoglobulinemia phenomenon is complex and laboratory typing is intriguing. Starting from this preliminary descriptive study, it will be possible, with the available data, to perform elaborations that allow to relate CRG with the diagnosis and verify the effect of therapy. Big Data methods' application represents an undeniable resource for public institutions when carrying out strategic decision-making processes. Disclosure of Interests: None declared